1994
DOI: 10.1159/000139246
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anesthetic and Convulsant Barbiturates on N-Methyl-D-Aspartate Receptor-Mediated Calcium Flux in Brain Membrane Vesicles

Abstract: The effects of anesthetic and convulsant barbiturates on brain N-methyl-D-aspartate (NMDA) receptor function were examined in a cell-free membrane vesicle preparation from mouse hippocampus. Increases in intracellular free calcium concentrations (Cai) were determined using a fluorescent dye, Indo-1 after stimulation with the NMDA receptor agonist, L-glutamate. Anesthetic barbiturates inhibited NMDA responses in a concentration-dependent manner with a rank order of potency of secobarbital > amobarbit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 14 publications
(14 reference statements)
1
11
0
Order By: Relevance
“…Phenobarbital has been used in some of the initial trials of pharmacotherapy for alcohol withdrawal and, in some studies, has been found to be superior to diazepam (56,67). Mechanistically, it is synergistic with benzodiazepines for GABA-A activation and in animals is capable of weakly inhibiting stimulatory NMDA receptors providing another potential benefit (68,69). The onset of action of a dose of phenobarbital is 20 -30 mins; therefore, caution must be used in dosing administration to avoid redosing before the peak affects have been achieved from the initial dose (67,70).…”
Section: Alternative Agentsmentioning
confidence: 99%
“…Phenobarbital has been used in some of the initial trials of pharmacotherapy for alcohol withdrawal and, in some studies, has been found to be superior to diazepam (56,67). Mechanistically, it is synergistic with benzodiazepines for GABA-A activation and in animals is capable of weakly inhibiting stimulatory NMDA receptors providing another potential benefit (68,69). The onset of action of a dose of phenobarbital is 20 -30 mins; therefore, caution must be used in dosing administration to avoid redosing before the peak affects have been achieved from the initial dose (67,70).…”
Section: Alternative Agentsmentioning
confidence: 99%
“…The barbiturate phenobarbital likewise acts on the glutamatergic system. This anesthetic inhibits NMDA receptor-mediated calcium influx (Daniell, 1994) and binding (Silva-Brum and Elisabetsky, 2000). Concomitant with phenobarbital binding to the GABAA receptor is an inhbition of AMPA receptor function (Joo et al, 1999).…”
Section: Actions Of Isoflurane and Phenobarbital Outside Of The Gabaementioning
confidence: 99%
“…In addition to anesthesia some of the barbiturates also induce convulsions (Daniell, 1994). Pentobarbital was used for many years as a soporific and anesthetic agent (O’Beirne et al, 1987) and has been suggested to be suitable for anesthesia of Biomphalaria tenagophila and B. glabrata (Martins-Sousa et al, 2001).…”
Section: Actions Of Clinical Anesthetics On Gastropod Molluscsmentioning
confidence: 99%